The revival of the Feldstein-Horioka Puzzle and moderation of capital flows after the Global Financial Crisis (2008/09) - Duran, H. E. (2022)
This study investigates the recent trend of the Feldstein-Horioka puzzle and the underlying reasons for moderation in capital flows. This issue is analysed quite inadequately for the period after the Global Financial Crisis, which represents a crucial turning point for economic climate and policies. The Feldstein-Horioka Puzzle is estimated using the World’s 13 largest economies, with panel GMM regression, between 1996 and 2016. We uncover that the Global Financial Crisis had a persistent detrimental effect on capital liberalization, after which the Feldstein-Horioka puzzle has revived and capital mobility has decreased. We suggest two possible explanations for such moderation in capital flows: the increasing risk perception and risk aversion behaviour of fund supplying countries, which increases the home bias, and capital controls against free flow of capital that have been applied after the Global Financial Crisis of 2008/2009.